2014 International Conference on Informatics, Networking and Intelligent Computing - Zhang, Jiaxing (CRC Press, 2015)
This proceedings volume contains selected papers presented at the 2014 International Conference on Informatics, Networking and Intelligent Computing, held in Shenzhen, China. Contributions cover the latest developments and advances in the field of Informatics, Networking and Intelligent Computing